The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/13691058.2016.1188420
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sexual behaviour among men and women in New York City area prisons

Abstract: The USA currently has the highest incarceration rate in the world. Individuals at greatest risk for HIV also tend to be among those at an elevated risk for incarceration. The HIV epidemic is driven by injection drug use and sexual behaviour, and estimates of prison-based sexual behaviour vary widely. This study examined sexual behaviour among 1,369 incarcerated men and women in the New York City area. Approximately 13 percent of the sample (n=176) reported being sexually active while incarcerated over the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…15 According to previous studies, women have more physical vulnerability to HIV and were at least twice as likely as men to contract HIV through sex. 16 Many of the women at highest risk for HIV infection are unaware of their risk, have little or no access to HIV prevention, and are afraid, for fear of violence, to ask their partners to use condoms. 13 The overall HIV infection rate has dropped from 2000 to 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 According to previous studies, women have more physical vulnerability to HIV and were at least twice as likely as men to contract HIV through sex. 16 Many of the women at highest risk for HIV infection are unaware of their risk, have little or no access to HIV prevention, and are afraid, for fear of violence, to ask their partners to use condoms. 13 The overall HIV infection rate has dropped from 2000 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…It was evident from some previous studies that out of all individuals diagnosed with HIV among the incarcerated population, a significant proportion got infected due to prison-based risky sexual behavior. 10,16,21,22 Voluntary and forced (prison rape) sexual behaviors, unregulated tattooing, and injection drug use led to a high risk of transmitting and contracting HIV infections. 20 Therefore, mandatory HIV screening at intake solely is not enough to detect the population getting infected during incarceration.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…A study of 1,369 men and women incarcerated in New York City identified that a significant proportion of the prisoners were sexually active and that most of them were not in the marital visitation program. This refers to the presence of sexual relationships within the prison environment, which occurred without the use of condoms, since they were not available to the prison population (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Given this scenario, knowledge about HIV and AIDS is referred to in the literature as an important tool for adopting self-care practices (6,9) , favoring prevention and reduction of risk behavior (10) , above all, in the prison population, whose deprivation of liberty reinforces the precariousness and fragility of the guarantee of sexual rights, due to the bureaucratic and structural limitations existing in the prison establishment (7)(8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation